2017
DOI: 10.1177/0003489417693014
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Markers in Surgically Treated HPV-Associated Oropharyngeal Cancer: Retrospective Study, Systematic Review, and Meta-analysis

Abstract: While many traditional clinico-pathologic markers of aggressive disease in head and neck cancer also impact survival in surgically treated HPV-associated oropharyngeal cancer, extracapsular extension may be less important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…However, there currently is a paucity of evidence showing the benefit postsurgical chemotherapy for HPV + OPSCC specifically. A meta‐analysis of eight studies with a total of 85 HPV + OPSCC patients with 85% receiving adjuvant therapy found T stage, nodal number, lymphovascular invasion, and PNI to be independent risk factors for disease recurrence but not ENE . Another NCDB study analyzing 2,454 HPV‐positive patients with 84% receiving adjuvant therapy found that ENE was associated with worse OS in HPV‐negative OPSCC patients but not HPV‐positive .…”
Section: Discussionmentioning
confidence: 99%
“…However, there currently is a paucity of evidence showing the benefit postsurgical chemotherapy for HPV + OPSCC specifically. A meta‐analysis of eight studies with a total of 85 HPV + OPSCC patients with 85% receiving adjuvant therapy found T stage, nodal number, lymphovascular invasion, and PNI to be independent risk factors for disease recurrence but not ENE . Another NCDB study analyzing 2,454 HPV‐positive patients with 84% receiving adjuvant therapy found that ENE was associated with worse OS in HPV‐negative OPSCC patients but not HPV‐positive .…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true when considering that extracapsular extension, which has been considered as a poor prognostic factor in OPSCC, was not associated with poor outcomes in several HPV-positive cohorts. 8,26,31,32 …”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis 31 on the pathologic markers in surgically treated HPV-positive patients with OPSCC included only 4 studies that examined PNI and ALI, and these preliminary data reveal no significant negative effect on survival. This same study 31 published prevalence data on PNI and ALI.…”
Section: Discussionmentioning
confidence: 99%
“…HPV detection and genotyping was carried out using the Multiplex HPV Genotyping Kit for Research in Epidemiology (Multimetrix, PROGEN Biotechnik, Heidelberg, Germany), as described previously [9], to apply an analytically sensitive technique that also allows low copy numbers of HPV DNA to be detected. The Luminex bead-based genotyping procedure allows detection of 15 high-risk types (16,18,31,33,35,39,45, 51, 52, 56, 58, 59, 68, 73, and 82), 3 putative high-risk types (26,53, and 66), and 6 low-risk types (6,11,42,43,44, and 70). Sections were evaluated for p16INK4a using immunohistochemistry as previously described [10].…”
Section: Hpv Statusmentioning
confidence: 99%
“…Therefore, the choice between CRT followed by salvage surgery or SRT as definitive primary treatment often depend on institutional biases and patient preferences. Results of pathological markers after SRT in HPV-associated OSCC have recently been published in a review, and T stage, nodal number, perineural invasion, and lymphovascular invasion were shown to have a significant impact on event-free survival [6]. In view of the excellent survival rates of HPV-driven OSCC, there is need for de-escalation of treatments since the toxicity of CRT is a major correlate of reduced quality of life [7], and is reported to be even higher in HPV-driven OSCC [8].…”
Section: Introductionmentioning
confidence: 99%